2023
DOI: 10.1039/d3se00998j
|View full text |Cite
|
Sign up to set email alerts
|

Selective placement of modifiers on hematite thin films for solar water splitting

Fabio A. Pires,
Gabriel T. dos Santos,
Jefferson Bettini
et al.

Abstract: The design of nanostructured materials for photoelectrochemical water splitting relies on a detailed understanding of the reactional bottlenecks. For hematite, a model system for photoanodes, the challenges concern poor charge...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Finally, one can see from Sn 4+ EDS mapping that no significant amount of tin diffused to the photoabsorbing hematite layer, supporting negligible interferences from Sn 4+ self-diffusion in the electrochemical measurements. 14…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, one can see from Sn 4+ EDS mapping that no significant amount of tin diffused to the photoabsorbing hematite layer, supporting negligible interferences from Sn 4+ self-diffusion in the electrochemical measurements. 14…”
Section: Resultsmentioning
confidence: 99%
“…Pires et al demonstrated an improvement in PEC performance by using Ga 3+ as a lattice dopant and Hf 4+ as an interfacial dopant. 14 Although they achieved a sevenfold increase in photocurrent in comparison to pristine hematite, here we draw the hypothesis that a knowledgeable selection of the dopants for both the crystalline lattice and interfaces can yield a more significant performance improvement by thoroughly exploring the novel synthetic protocol while also considering sustainability matters.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…RHE. Another new and more effective strategy, introduced by Pires et al 125 involves the selective placement of modifiers. Here, they present a novel approach using a single polymeric precursor solution for the design of α-Fe 2 O 3 with synergistic bulk and interfacial engineering involving Ga 3+ , Hf 4+ , and NiFeO x .…”
Section: Strategies For Charge Separation Modification In the Bulk Su...mentioning
confidence: 99%